Prenylated flavanones from Derris reticulata - Chulabhorn Mahidol (2018)
Two new pyranoflavanones, 2''',3'''-epoxylupinifolin and dereticulatin, together with the known flavonoid lupinifolin, were identified from the stems of Derris reticulata. The structures and NMR spectral data were assigned by the use of 2D NMR technology and chemical transformations. All of the isolates showed cytotoxic activity in the P-388 cell line.